Play as a way of being for the work of art: reflections upon artistic representation in gadamer’s hermenutic aesthetics (2013)
Within critical hermeneutics, this article presents Gadamercritique to the subjectivization of aesthetics andthe notion of ‘play’ as a counterconcpet to the categoryof subject. The ludic onlthology of the work of art isalso presented conceived as ‘self-representation’ or‘re-presentation’ of someone. This provides a link tothe notion of mimesis and a reflection on the value ofthruth and knowledge in the wowrk of art.